Origin of the earth and moon - Canup, R. M. (Robin M.), 1968-; Righter, K. (Kevin), 1965- (University of Arizona space science series., 2000)
The age-old question of how our home planet and its satellite originated has in recent times undergone a minor revolution. The emergence of the "giant impact theory" as the most successful model for the origin of the Moon has been difficult to reconcile with some aspects of the Earth, and the development of an integrated model for the origin of the Earth-Moon system has been difficult for this reason. However, recent technical advances in experimental and isotopic work, together with intensified interest in the modeling of planetary dynamics, have produced a wealth of new results requiring a rethinking of models for the origin of the Earth and Moon. This book is intended to serve as a resource for those scientists working closely in this field, while at the same time it provides enough balance and depth to offer an introduction for students or technically minded general readers. Its thirty chapters address isotopic and chemical constraints on accretion, the dynamics of terrestrial planet formation, the impact-triggered formation of the Earth-Moon system, differentiation of the Earth and Moon, the origin of terrestrial volatiles, and conditions on the young Earth and Moon. Covering such subjects as the history and origin of the Moon's orbit, water on the Earth, and the implications of Earth-Moon interactions for terrestrial climate and life, the book constitutes a state-of-the-art overview of the most recent investigations in the field. Although many advances have been made in our ability to evaluate competing models of the formation of the Earth-Moon system, there are still many gaps in our understanding. This book makes great strides toward closing those gaps by highlighting the extensive progress that has been made and pointing toward future research.